The Role of TNF-α and TNF Superfamily Members in the Pathogenesis of Calcific Aortic Valvular Disease. (6th November 2013) - Galeone, Antonella; Paparella, Domenico; Colucci, Silvia; Grano, Maria; Brunetti, Giacomina
Abstract : Calcific aortic valve disease (CAVD) represents a slowly progressive pathologic process associated with major morbidity and mortality. The process is characterized by multiple steps: inflammation, fibrosis, and calcification. Numerous studies focalized on its physiopathology highlighting different "actors" for the multiple "acts." This paper focuses on the role of the tumor necrosis factor superfamily (TNFSF) members in the pathogenesis of CAVD. In particular, we discuss the clinical and experimental studies providing evidence of the involvement of tumor necrosis factor-alpha (TNF- α ), receptor activator of nuclear factor-kappa B (NF- κ B) ligand (RANKL), its membrane receptor RANK and its decoy receptor osteoprotegerin (OPG), and TNF-related apoptosis-inducing ligand (TRAIL) in valvular calcification.